al-ʻAqīdah, al-sharīʻah, al-taṣawwuf ʻinda al-Imām al-Junayd Abī al-Qāsim al-Khazzāz al-Baghdādī, 215-297 H/830-909 M - ʻAbd al-Salām Muḥammad al-Bakkārī, author (Maghribi : Markaz al-Turats al-Tsaqofy, 2008)
Includes bibliographical and references